Performance Evaluation of the Drainage System at FMIPA University of Lampung under Extreme Rainfall Conditions (Journal of Applied Science, Engineering and Technology, 2025)
Urban drainage systems are facing increasing challenges due to the intensification of extreme rainfall caused by climate change and rapid urban development. This study aims to evaluate the performance of the drainage system at the Faculty of Mathematics and Natural Sciences (FMIPA), University of Lampung, in managing flood discharge during extreme rainfall events. Using 24 years of rainfall data, the design rainfall was calculated using the Gumbel distribution and converted into short-duration intensity using the Mononobe method. Peak discharge was estimated with the Rational method, and compared against the channel capacity calculated using Manning’s equation. The results showed that the designed trapezoidal drainage channel (0.4 m × 1.2 m × 0.6 m) could safely convey runoff from a 25-year return period. However, field observations revealed that the installed channel at several points, particularly DN65 (0.35 m × 0.40 m), was undersized and could not accommodate the peak flow. This discrepancy highlights the need for upgrading existing drainage infrastructure on campus.